TRAINING OF A MODERN SPECIALIST IN THE CONDITIONS OF DIGITAL PROFESSIONAL EDUCATION - Sergeeva, Marina; Lukashenko, Dmitry; Ragimov, Telman; Chauzova, Vera; Kunitsyna, Maria (Revista Inclusiones, 2020)
The current economic situation is characterized by increased risk, uncertainty and dynamism of the modern world. Professional education is seriously affected by these changes, which influences the fluctuations of demand for specialists of different profiles. This demand comes from the direct requirements of the established market and focuses on the development of a specialist’s adaptive capabilities in the modern conditions. A modern specialist has to adapt to the labor market, which is characterized by a sharp reduction in demand for low-skilled workers; the emergence of an elite layer of workers who maintain complex electronic and automatic equipment; a reduction in the number of blue-collar workers and an increase in the personnel engaged in design, processing, marketing; the priority of workers who have skills in handling modern office equipment and computers, who have a good command of foreign languages in the field of their profession; the need for managers who are able to organize team work, plan human and material resources most efficiently; the demand for specialists who are able to work at the level of professional excellence from the first days of their independent activity. The market of educational services is now actively improving, which encourages educational institutions to reconsider their approach to the training of professional personnel. The teacher has to rationally use such teaching methods that will ensure the training of qualified specialists who will become competitive in the labor market. The diversity of these methods and techniques should arouse students’ interest in the educational and cognitive activity.